Health and mass unemployment events—developing a framework for preparedness and response. (5th October 2018) - Davies, A R; Homolova, L; Grey, C N B; Bellis, M A
Abstract: Background: Mass unemployment events are not uncommon yet the impact on health is not well recognised. There is a need for a preparedness and response framework, as exists for other events that threaten population health. Methods: Framework informed by a narrative review of the impact of mass unemployment on health (studies published in English from 1990 to 2016), and qualitative data from 23 semi-structured interviews with individuals connected to historical national and international events, addressing gaps in published literature on lessons learnt from past responses. Results: Economic and employment shock triggered by mass unemployment events have a detrimental impact on workers, families and communities. We present a public health informed response framework which includes (i) identify areas at risk, (ii) develop an early warning system, (iii) mobilise multi-sector action including health and community, (iv) provision of support across employment, finance and health (v) proportionate to need, (vi) extend support to family members and (vii) communities and (viii) evaluate and learn. Conclusion: Mass unemployment events have an adverse impact on the health, financial and social circumstances of workers, families, and communities. This is the first framework for action to mitigate and address the detrimental impact of mass unemployment events on population health.